Knowledge, Attitudes, and Food Safety Practices of Informal Market Maize Grain Vendors and Consumers in Meru County, Kenya - Cherotich Cheruiyot; Michael W. Okoth; George O. Abong’; Sarah W. Kariuki (International Journal of Food Science)
Aflatoxin contamination in food poses a significant health risk, especially in low- and middle-income nations. While there is a need to increase food safety, there is a lack of aflatoxin-related sociodemographic factors, knowledge, attitudes, and practices (KAPs) among aflatoxin-risk populations. The study is aimed at collecting information from the vendors and consumers of maize grains to investigate their sociodemographic factors and KAPs of aflatoxin contaminations in Kenya’s small- and medium-sized informal markets. A cross-sectional survey using a simple random sampling approach was conducted from July 2022 to August 2022 in Meru County, Kenya. Vendors and consumers of maize grain markets were interviewed using face-to-face interviews and semistructured questionnaires. Females were the predominant gender among the maize grain vendor (82.7%) and consumer (83.72%) participants. Most vendors (95.7%) and consumers (94.2%) have formal education. Almost all vendors (96.2%) and consumers (95.3%) check for maize selling and purchasing quality. The proportion of visibly mouldy grains (25.5%, 29.0%), moisture level (20.2%, 12.9%), and size of grains (11.4%, 14.8%) were the commonest quality dimensions checked by vendors and consumers, respectively. Most vendors (86.8%) and consumers (70.9%) have heard about aflatoxin, but only 48.2% of the vendors and 52.1% of the consumers were aware and could mention the correct aflatoxin health effects. Vendors’ and consumers’ KAPs on aflatoxin varied significantly (p<0.05) across subcounties, education levels, genders, and ages. Promoting public awareness, building capacity, and implementing aflatoxin-related policies at all levels are crucial to ensure food safety.